Green Office, Green Hospital dan Kaitannya Dengan Perubahan Iklim - Wardhani, Indra Sari (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45504037/Green-Office-Green-Hospital-dan-Kaitannya-Dengan-Perubahan-Iklim